Gambaran Pasien Gangguan Spektrum Autisme di Poliklinik Tumbuh Kembang Anak RSUD Abdoel Wahab Sjahranie Periode 2019 - 2022 - Maneng Mangallo, Jeane Triamin; Fitriany, Evi; Supit, Diane Meytha (ITKES Wiyata Husada Samarinda, 2023)
Autism Spectrum Disorder as one of the most frequently neurodevelopmental disorder occurred before the age of three. This study is conducted to description of patients with autism admitted to Pediatric Growth and Development Polyclinic at Abdoel Wahab Sjahranie Hospital in Samarinda from 2019 to 2022 according to their group of age, sex, nutritional status, family history, gestational age, and birth weight. This study applied a retrospective descriptive design and total sampling method with data obtained from medical records. The findings showed that 66 child patients were diagnosed with autism were at the age group between 1 and 5 (81.8%) and most of them were male (69.7%). Nutritional status was measured based on 2006 WHO chart for the age group between 1 month and 5 years old in good nutrition (35%) and 2000 CDC for the age group older than 5 years old in normal nutrition status (38.5%). Almost all patients showed no family history (89,4%), were born with term gestational age (74,2%) and normal birth weight (94%). In conclusion, patients with autism mostly categorized into the age group between 1 and 3, male, normal nutritional status, without autism family history, term gestational age, and normal birth weight.